Evaluación de la Factibilidad Técnica, Económica y Ambiental de las nuevas alternativas tecnológicas para la aplicación de Mucílagos en la Agroindustria - Lara Atiaja, Josselin Elizabeth (2020)
The magnitude of this project lies in the fact that the technical, economic and environmental feasibility of the mucilage applications in the different agro-industrial processes is determined from the research carried out, for this it was based on the academic documentation of the projects carried out in the Career of Agroindustry. Projects in which mucilaginous plants were used as the main component of analysis for the improvement of the physical, chemical, microbiological and organoleptic characteristics; product used as a clarifier, stabilizer and biodegradable coating. To determine the technical feasibility, an analysis of the different projects in which an evaluation of the methods, techniques and materials used was performed; Likewise, an analysis and bibliographic comparison of the results obtained by the authors with other related projects was elaborated, in this way, it was concluded that these projects are technically feasible. In the same way, the budgets described in the projects were